Costs Syndrome in Children, Causes, Comparative Diagnosis and Rational Therapy (Review of the article) (The Peerian Journal, 2022)
This publication deals with topical problems in the management of patients with cough. It presents its epidemiology and clinical classification, an analysis of its causes, a list of required diagnostic techniques, and areas of pharmacotherapy. Emphasis is laid on the differential diagnosis of different abnormalities and diseases, the leading clinical sign of which is cough. The authors provide the detailed characteristics of medicaments for its treatment and the principles of rational antitussive and mucoactive pharmacotherapy.